2017
DOI: 10.1371/journal.pone.0179815
|View full text |Cite
|
Sign up to set email alerts
|

Effective new membrane for preventing postthoracotomy pleural adhesion by surface water induction technology

Abstract: BackgroundAfter thoracic surgery, adhesions between the pleura can cause substantial complications. This study investigated the effectiveness of a novel membrane utilizing surface water induction technology to prevent adhesions.MethodsEight beagles were divided into an experimental group (five males) and a control group (three females). The experimental group underwent thoracotomy on both the left and right sides of the chest. Both sides received the membrane, and the membrane on one side was glued to the pleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…An insoluble hyaluronic acid membrane containing glycerol has been developed that shows greater effects in preventing postoperative adhesions after thoracic surgery than the above-mentioned carboxymethyl-cellulose membrane 25 . In a previous study in which thoracotomy was performed in dogs with the use of a novel membrane that uses surface water induction technology to prevent adhesions (insoluble hyaluronic acid membrane), we also showed that this membrane is effective in preventing postoperative adhesions after thoracotomy 26 .…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…An insoluble hyaluronic acid membrane containing glycerol has been developed that shows greater effects in preventing postoperative adhesions after thoracic surgery than the above-mentioned carboxymethyl-cellulose membrane 25 . In a previous study in which thoracotomy was performed in dogs with the use of a novel membrane that uses surface water induction technology to prevent adhesions (insoluble hyaluronic acid membrane), we also showed that this membrane is effective in preventing postoperative adhesions after thoracotomy 26 .…”
Section: Introductionsupporting
confidence: 54%
“…The day of implantation was specified as day 1 of observation. At the time of sacrifice when the chest was re-opened, adhesions, if present, were dissected macroscopically using Kelly forceps, Metzenbaum scissors, and cotton swabs, and the strength of adhesions was evaluated and scored based on the degree of bluntness or sharpness of the dissection process (0=no need to dissect; 1=film-like adhesion, can be dissected easily; 2=mild adhesion, can be dissected; 3=moderate adhesion, difficult to dissect; 4=strong adhesion, impossible to dissect), using the same scoring systems as in a previous report 26 . The macroscopic findings of adhesions after thoracotomy were compared statistically by comparing the adhesion scores of the Experimental group and the Control group using the Mann-Whitney U test.…”
Section: Methodsmentioning
confidence: 99%
“…Two weeks after thoracotomy in dogs, the insoluble hyaluronic acid membrane was completely absent in the thoracic cavity in some animals, while a liquefied substance was observed in others. 4,13 Moreover, the insoluble hyaluronic acid membranes were not observed in any of the dogs that underwent repeat thoracotomy 10 weeks after initial thoracotomy. 14 However, these studies only verified the morphological changes of insoluble hyaluronic acid in the thoracic cavity after the period during which postoperative adhesions form.…”
Section: Introductionmentioning
confidence: 94%
“…We used hyaluronic acid, which is safer than glycerin. We additional used the surface water induction technology, as described by Noishiki et al, and found that hyaluronic acid had a high adhesion-prevention effect after thoracotomy in dogs (16). After pleural surgery using insoluble hyaluronic acid creates a physical barrier, preventing adhesions from forming during the postoperative period (17).…”
Section: Editorialmentioning
confidence: 99%
“…After pleural surgery using insoluble hyaluronic acid creates a physical barrier, preventing adhesions from forming during the postoperative period (17). Insoluble hyaluronic acid causes few shortterm (16,18) and mid-term (19) intrapleural inflammatory responses. This is likely attributable to the excellent ability of insoluble hyaluronic acid to act as a physical barrier.…”
Section: Editorialmentioning
confidence: 99%